Empowering Creativepreneurs for Economic Development: Learning Strategies in Equivalency Education Programs - Erwin Erlangga; Alex Sujanto; Arumwardhani Nusandari; Prita Febriani (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study examines the effectiveness of learning strategies aimed at enhancing creativepreneurship within equivalency education programs using a quantitative research approach. A sample of 150 students from various centers participated, with data collected through a structured questionnaire assessing the impact of interactive and project-based learning strategies on entrepreneurial creativity and skills. The findings reveal a significant positive correlation between the use of these strategies and the development of creative thinking, problem-solving abilities, and entrepreneurial initiative. Additionally, demographic factors such as age and prior education moderated the outcomes, highlighting the importance of tailored approaches in fostering creativepreneurship. These insights offer valuable guidance for educators and policymakers seeking to improve the effectiveness of equivalency education programs in promoting entrepreneurial capabilities among diverse learners.